Study of atmospheric effect in free space optic propagation - Abdul Rahman, Kram (Universiti Malaysia Perlis, 2011)
Free Space Optic (FSO) telecommunication system is Line of Sight (LOS) system which refer to transmission of visible and infrared beams that through to atmosphere to obtain the optical communication. This system uses laser to transmit the data in free space. However this system is vulnerable with variation of air turbulence particles that occurs in atmosphere. This thesis is aim to investigate the attenuation effect over the point-to-point FSO communication linkage. The study carried out under the tropical rainforest climate and the sample data is take at Perlis region that provide by Malaysia Meteorological Department (MMD). There two type of weather condition that capable to impair the FSO link performance. The first is rain weather where the rainfall occurs in tropical rainforest region almost everyday and has a high rain denseness rate. The second is haze weather which is usually contributed by smoke that produced from open burning of agriculture. The continuous burning and in wide area have produce the high density of haze to environment weather which create limited distance for visibility. Consequently, haze and rain can contribute to high atmospheric attenuation and predicted capable to impair the FSO link performance. Two approaches have been used in this research. The first is modeling the rain and haze attenuation to investigate the Perlis weather pattern in order to determine how strong the attenuation can occur in FSO communication linkage. This atmospheric model for haze and rain are constructed from scattering coefficients, atmospheric attenuation and geometric loss equation. The second approach is develop the FSO system using the OptiSystem to observe the effects attenuation over the link system. The performance of this FSO system is investigate under different parameters wavelength, size of aperture for transmitter and receiver, beam divergence angle and receiver sensitivity. The result from this research shows the haze weather effect is worst than rain where the maximum haze and rain attenuation can reach 180 dB/km and 96 dB/km respectively. At aim distance 1km operational for FSO deployment the prediction maximum visibility haze is 0.8km and rainfall rate is 70mm/hr. Meanwhile in simulation analysis shows that the longer wavelength 1550nm is much better than 785nm. The Design 1 for receiver aperture size 0.25m and transmitter aperture size 0.05m can reduce the loss. 5arrow beam divergence angle can reduce the power consumption and maintain the high power at receiver and also the APD photodiode is much better than p-i-n photodiode due to have high sensitivity to detect weak signal.